Effects of External Parasites on the Productivity of Poultry in the Traditional Rearing System in the Sub-humid Zone of Burkina Faso - Hien, O.C.; Diarra, B.; Dabire, R.; Wangrawa, J.; Sawadogo, L. (International Journal of Poultry Science, 2011)
This study was designed to identify the external parasites and to evaluate their effects on mortality, growth and reproduction of poultry in the traditional rearing system in the sub-humid zone of Burkina Faso. Identification of external parasites was done on 500 of each species of chicken, guinea fowls and turkeys. For the evaluation of the effects of external parasites on the productivity of poultry, 324 chicks that were 6 weeks of age were randomly divided into 12 groups of 27 chicks each. Four of the groups was assigned at random to receive a treatment against external parasites (ET), 4 other groups were similarly assigned to receive a treatment against external parasites and another treatment against internal parasites (EIT). The 4 remaining groups were not treated against parasites (NT). Two mice species Liperus gallinae and Monopon gallinae have been found on both chicken and turkeys while Goniodes gigas was the only mice species parasiting chicken. The lice Echidnophaga gallinacea and the tick Argas persicus have been found to parasite chicken. Results of productivity trial showed that mortality due to effects of external parasites amounted to 13.9% of non treated poultry. Live weight of male birds increased from the base line of 850 g of the non-treated birds by 9.8% (950±164.3 g) due to treatment against external parasites and by 44.5% (1250±133.1g) due to treatments against both external and internal parasites. Live weight of female birds increased similarly from 952.5±238.7 g by only 3.8% (980.5±36.2 g) due to treatment against external parasites and then by 13.5% (1081.6±160.2 g) due to treatment against both external and internal parasites. Likewise, age at first egg decreased from 28 weeks to 25 weeks with treatment against external parasites and further to 24 weeks with both treatments. Egg weight also increased from 47 to 48.0g due to treatment against external parasites and further to 48.5g due to both treatments. External parasites increase mortality rate and reduce growth rate of chicken.